GameAlfa: jogo digital como recurso tecnológico para alunos em processo de alfabetização do segundo ano do ensino fundamental - Santos, Austonio Queiroz dos (2018)
This research investigated the use of a game as a facilitating resource of alphabetization, by the developing of phonologycal awereness skills in students od the second year of middle school, in a public school of Manaus. During the metodologycal path, we adopted the qualitative approach having the action-research as the method; the technics and the data collections instruments used were the bibliografic research, the participant observation and the questionary adapted in a test shape. As the main resource was created a game during the invetisgatory path and applied to the class of students. With the application of a prototype, were collected the suggestions of the students and the teacher and applied again with the suggested amendments, searching with this a collaborative process of investigation and of product criation. The results verified were satisfying, because shows the development of phonologycal awereness skills in most of the studentes participating on the research, stem from the use of GameAlfa as technologycal resource.